Assessment of Power Quality Indicators in Electrical Networks Connected to Distributed Generation Sources - Muratov Kh.M; Tolipov J.N; Saidov A.H (Zien Journals, 2025)
This article is devoted to the assessment of power quality indicators in electrical networks connected to distributed generation sources. It discusses key parameters necessary to ensure power quality, such as voltage stability, frequency control, power flows, and harmonics. The article notes that distributed generators can inject power from various sources into the grid, which may lead to changes in network parameters. Therefore, it emphasizes the need for continuous monitoring of network quality. The article also presents the permissible normative values for voltage and current harmonic components. It concludes that, for reliable and stable operation of the power network, the output parameters of distributed generators must remain within established limits
Keywords: distributed generation; power quality; voltage stability; frequency control